Use of Seton in Management of High Variety of Anal Fistula - Alam, Mohammad Noor A; Abbasi, Sharmin (Anwer Khan Modern Medical College Journal, 2017)
Background: Anal fistula is an abnormal communicative small channel that has an internal opening and an external opening and connected by the primary track. Our study evaluate the effectiveness of seton in high variety anal fistula. Objectives: Evaluation the efficacy and safety of seton as surgical management of high anal fistula. Methods: This is a prospective study done on 57 patients in BIRDEM hospital and some other clinic of Dhaka city in 3 years period with high variety of anal fistula which is above the dentate line and were treated with seton .Outcome measured during follow up period were- successfully healed, recurrence, incontinence, percentage of complications and patients satisfaction. Result: Among 57 patients mean age was 38.2+_6.8 years. Overall outcome of the patients showed-fistula completely healed in 51 patients, incontinence occurred in 2 patients and recurrence occurred in 4 patients. Conclusion: Seton is relatively safe, effective and low cost for the management of high anal fistula with low rate of incontinence. It can therefore, be recommended as the standard of treatment for high variety fistula in ano. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 100-104